Answer:
x=0,-3
Step-by-step explanation:
x(x+3)(x+3)=0
Using the zero product property
x=0 x+3=0 x+3 =0
x=0 x=-3 x=-3
A) Tangent is positive in Quadrant I.
Since sine and cosine are both positive in Quadrant I and tangent is the ratio of sine to cosine, tangent is positive in Quadrant I
Step-by-step explanation:
Using synthetic division of polynomials 3x⁴-2x²+4x+9÷x+2. Rewrite the dividend as 3x⁴+0x³-2x²+4x+9
2 | 3 0 -2 4 9
| 6 -12 20 -32
3 -6 10 -16 41
So the quotient is 3x³-6x²+10x-16 with a remainder of 41
Therefore, 3x³-6x²+10x-16+(41/x+2)
1.Centigrams are larger than decigrams: NO
2.Hectometers are smaller than kilometers: YES
3.Dekaliters are larger than kiloliters: NO
.4.Grams are smaller than dekagrams: YES
4x^2-5x=-1
4x^2-5x+1=0
4x+2.24x=1
6.24x=1
x= 0.16025641025641025641025641025641